2012
DOI: 10.3920/wmj2011.1348
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of toxigenic Fusarium graminearum in wheat

Abstract: Fusarium graminearum (Schwabe) contaminates agricultural crops and commodities with trichothecenes, mostly deoxynivalenol and its acetyl-derivatives. Current techniques available to detect final mycotoxin contamination products usually require an extended time lag between sampling and the corresponding report, and include different clean-up steps and eventually derivatisation. This study was aimed to develop a methodology to detect toxigenic F. graminearum prior to mycotoxin production. Headspace solid-phase m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…graminearum metabolite examinations have been carried out on different media (Jeleń et al ., ; Girotti et al ., ). Experiments were also conducted in field experiments where spikes of cereals were inoculated (Perkowski et al ., ; Girotti et al ., ). The experiment performed by Jeleń et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…graminearum metabolite examinations have been carried out on different media (Jeleń et al ., ; Girotti et al ., ). Experiments were also conducted in field experiments where spikes of cereals were inoculated (Perkowski et al ., ; Girotti et al ., ). The experiment performed by Jeleń et al .…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by data demonstrating the general regulatory character of Tri6 not only in enhancing the trichothecene genes but also regulating genes involved in the isoprenoid pathway and other genes (Merhej et al ., ). Some of the VOCs are characteristic for fungi belonging to the genus Fusarium and even for toxigenic isolates only (Jeleń et al ., ; Demyttenaere et al ., ; Buśko et al ., ; Girotti et al ., , ). These VOCs mainly belong to the terpenes, but they are also low‐molecular‐weight compounds belonging to other chemical groups such as pentane, oct‐3‐en‐2‐ol or heptanol (Olsson et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…During the observation period (7-10 days) its content in the equilibrium vapor above culture F. culmorum changed only slightly. Among sesquiterpenes, typical fusaric fungi [17], only 0.2% sativene was detected. Trichodiene and the sesquiterpene hydrocarbons with a molecular weight of 204 in amounts exceeding 0.1% of the total amount of VOCs were not detected.…”
Section: Retention Time Minmentioning
confidence: 98%
“…Trichodiene and the sesquiterpene hydrocarbons with a molecular weight of 204 in amounts exceeding 0.1% of the total amount of VOCs were not detected. It was shown that trichodiene is the most abundant volatile metabolite of the sesquiterpene series in trichothecene-producing fungal species [17,18].…”
Section: Retention Time Minmentioning
confidence: 99%
“…Examinations of metabolites which are considered as fungal biomass markers—ERG and ATP are also of great importance. What is most interesting are the results that indicate a correlation between these markers and mycotoxins (Borjesson et al, 1992; Perkowski et al, 2007) and their relationship with volatile compounds (Demyttenaere et al, 2004; Sahgal et al, 2007; Girotti et al, 2012; Buśko et al, 2014). …”
Section: Introductionmentioning
confidence: 99%